Biomass burning in Indo-China peninsula and its impacts on regional air quality and global climate change-a review. (August 2017) - Yadav, Ishwar Chandra; Linthoingambi Devi, Ningombam; Li, Jun; Syed, Jabir Hussain; Zhang, Gan; Watanabe, Hirozumi
Abstract: Although, many biomass burning (BB) emissions products (particulate matter and trace gases) are believed to be trans-boundary pollutants that originates from India and China (the two most populous countries in Asia), the information about BB emission and related contents is limited for Indo-China Peninsula (ICP) region. This motivated us to review this region pertaining to BB emission. The main objective of the review is to document the current status of BB emission in ICP region. In order to highlight the impact of BB on regional air quality and global climate change, the role of BB emission in ICP region is also discussed. Based on the available literature and modeling simulations studies, it is evidenced that ICP is one of the hotspot regional source for aerosols in terms of BB emissions. In addition, regional emissions through BB have significant implications for regional air quality especially in the neighboring countries such as China, Taiwan and India. Our assessment highlight that there is still a general lack of reliable data and research studies addressing BB related issues in context of environmental and human health. There is therefore a critical need to improve the current knowledge base, which should build upon the research experience and further research into these issues is considered vital to help inform future policies/control strategies. Graphical abstract: Highlights: Forest burning is the main sources of BB emissions in the ICP region. ICP is one of the hotspot regional source for aerosols in terms of BB emissions. BB emission in ICP significantly affects regional air quality and global climate. Abstract : Indo-China Peninsula is one of the hotspot sources of aerosols in terms of biomass burning emissions that significantly influence regional air quality and global climate change.